PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS LOCAL WISDOM DAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA SD - Berliana, Herlin; Widiarti, Nuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop and examine the effectiveness of an interactive e-module integrated with local wisdom and Problem Based Learning (PBL) to enhance elementary school students’ critical thinking skills in learning IPAS, particularly on the topic of changes in the states of matter. The research employed a research and development (R&D) approach, encompassing needs analysis, product design, development, expert validation, revision, and field testing. The product was validated by experts in content, media, and language to ensure its feasibility before implementation. The effectiveness of the e-module was tested using a quasi-experimental design involving an experimental class and a control class. Data were collected through critical thinking pretests and posttests and analyzed using normality tests, homogeneity tests, independent and paired t-tests, and N-Gain analysis. The results indicated that the data met the assumptions for parametric testing. Findings revealed a significant improvement in students’ critical thinking skills in the experimental class compared to the control class. The experimental group achieved a higher N-Gain score, indicating that the interactive e-module integrated with local wisdom and PBL was more effective than conventional learning. These results suggest that integrating local cultural contexts with problem-based learning and interactive multimedia can create meaningful learning experiences and effectively foster critical thinking skills in elementary science education